P193 Management of patients with HIV and Hepatitis C co-infection at a small teaching hospital; an audit against 2013 BHIVA guidelines. (30th June 2016) - Gaddie, Jessica; Reeves, Iain; Croucher, Adam
Abstract : Background/introduction: HIV positive patients with Hepatitis C (HCV) progress to cirrhosis faster than patients without HIV. BHIVA guidelines 2013 recommend surveillance for cirrhosis and hepatocellular carcinoma. Aim(s)/objectives: To evaluate the management of patients with HCV and HIV co-infection against current guidelines for surveillance for liver disease, including with Liver Transient Elastography (TE). Methods: The clinical records of all patients with HIV and HCV co-infection in the last 10 years were reviewed. Results: 41 patients had co-infection; 6 patients spontaneously cleared HCV. 100% (41/41) of all new diagnoses of HCV received HCV RNA measurement. Genotyping carried out in 86% (30/35) of patients and not possible in 6 cases. Annual HCV RNA was carried out in 76% (29/38). Only 8% (3/36) cases had initial TE result. In 17/36 the result was not recorded, and there was no evidence that the TE had been carried out. In 14/36 the patient did not attend the tertiary centre. Two of the initial TEs were reported as normal (less than 7 kPa). For annual TE assessments, 5/36 were reported. Discussion/conclusion: Most patients reviewed did not have assessment for liver disease per national guidelines. Our monitoring of patients with HCV and HIV co-infection particularly with liver TE is poor. The main barrier to co-infected patients receiving care is non-attendance at the tertiary centre. The Trust is now a "spoke" in a hepatitis C network and has local TE, which may improve monitoring of co-infected patients. We will re-audit after this programme has been running for one year.